sabendo-se que g(f(x)) = e = , determine f(5) + g .
Usuário anônimo:
é derivada?
Soluções para a tarefa
Respondido por
2
Se g^-1 = (2x +1)/(1 - x), então:
x = (2g +1)/(1 - g)
x - xg = 2g + 1
2g + xg = x - 1
g.(2 + x) = x - 1
g = (x - 1)/(x + 2)
Se g(f(x)) = (2x - 2)/(2x + 2), então:
(f - 1)/(f + 2) = (2x - 2)/(2x + 2)
(f - 1)/(f + 2) = (x - 1)/(x + 1)
(f - 1).(x + 1) = (f + 2).(x - 1)
fx + f - x - 1 = fx - f + 2x - 2
2f = 3x - 1
f = (3x - 1)/2
Queremos f(5) + g(-7/2):
(3.5 - 1)2 + (- 7/2 - 1)/(- 7/2 + 2) =
14/2 + (- 9/2)/(- 3/2) =
7 + (9/2).(2/3) =
7 + 9/3 =
7 + 3 =
10.
x = (2g +1)/(1 - g)
x - xg = 2g + 1
2g + xg = x - 1
g.(2 + x) = x - 1
g = (x - 1)/(x + 2)
Se g(f(x)) = (2x - 2)/(2x + 2), então:
(f - 1)/(f + 2) = (2x - 2)/(2x + 2)
(f - 1)/(f + 2) = (x - 1)/(x + 1)
(f - 1).(x + 1) = (f + 2).(x - 1)
fx + f - x - 1 = fx - f + 2x - 2
2f = 3x - 1
f = (3x - 1)/2
Queremos f(5) + g(-7/2):
(3.5 - 1)2 + (- 7/2 - 1)/(- 7/2 + 2) =
14/2 + (- 9/2)/(- 3/2) =
7 + (9/2).(2/3) =
7 + 9/3 =
7 + 3 =
10.
Respondido por
0
.. . . .. . . . . .. . . . . .. . . . . . .. . . .
Perguntas interessantes